Pertunjukan Musik Solis Marimba dan Ensambel Perkusi dengan Repertoar Concerto In E Minor For Solo Marimba, Can You Feel The Love Tonight, dan Journey To Deli (Marimba Solis Music Show and Percussion Ensemble with Repertoire Concerto In E Minor For Solo Marimba, Can You Feel The Love Tonight, and Journey To Deli) - Akmal, Muhammad Fauzan; Herdianto, Ferry; Hendri, Yon (Institut Seni Indonesia Padangpanjang, 2023)
ABSTRAKRepertoar musik dari berbagai era seperti classic, popular dan melayu dikemas ke dalam sebuah pertunjukan solis marimba dengan menggunakan kaidah pertunjukan konvensional.Repertoar dalam pertunjukan ini terdiri dari repertoar berbagai era.Repertoar pertama dalam pertunjukan adalah repetoar era klasik yang berjudul Concerto in E minor For Solo Marimba dengan komposer Braedon Bomgardner.Repertoar kedua adalah Can You Feel The Love Tonight yang merupakan lagu popular animasi disney ciptaan Elton John. Repertoar terakhir dengan judul Journey To Deli karya dari Tengku Ryo Riezkan. Penyaji menginterpretasikan berbagai teknik seperti legato, arpegio, triol, single stroke roll, roll, dan improvisasi untuk mewujudkan tercapainya sebuah pertunjukan yang utuhKata kunci : Pertunjukan, Marimba, Solis ABSTRACTMusic repertoire from various eras such as classic, popular and Malay is packaged into a solo marimba performance using conventional performance rules. The repertoire in this show consists of repertoires of various eras. The first repertoire in the show is the classical era repertoire entitled Concerto in E minor For Solo Marimba with composer Braedon Bomgardner. The second repertoire is Can You Feel The Love Tonight which is a popular song by Elton John. The last repertoire with Journey To Deli by Tengku Ryo Riezkan. Presenters interpret various techniques such as legato, arpegio, triol, single stoke roll, roll, and improvisation to achieve a complete performance.Keywords: Performance, Marimba, Solis